2009
DOI: 10.1074/mcp.m800326-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

The Retinal Proteome in Experimental Diabetic Retinopathy

Abstract: Diabetic retinopathy is the leading cause of blindness in working age persons. Targeted studies have uncovered several components of the pathophysiology of the disease without unveiling the basic mechanisms. This study describes the use of complementary proteomic and genomic discovery methods that revealed that the proteins of the crystallin superfamily are increased dramatically in early diabetic retinopathy. Orthogonal methods confirmed that the amplitude of the up-regulation is greater than other changes de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 42 publications
7
48
1
Order By: Relevance
“…This pattern of expression is consistent with previous reports in animal models of diabetes (6,26) as well as other neurodegenerative models primarily affecting the inner retina, such as ischemic neuropathies, optic nerve crush, and glaucoma (27). This expression pattern is consistent with studies suggesting a central role for αA-and αB-crystallin in the neuroglial unit in neurodegenerative diseases.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This pattern of expression is consistent with previous reports in animal models of diabetes (6,26) as well as other neurodegenerative models primarily affecting the inner retina, such as ischemic neuropathies, optic nerve crush, and glaucoma (27). This expression pattern is consistent with studies suggesting a central role for αA-and αB-crystallin in the neuroglial unit in neurodegenerative diseases.…”
Section: Discussionsupporting
confidence: 81%
“…In addition to our data in animal models (6,17), recent reports have suggested that α-crystallins also accumulate in ocular tissues of diabetic patients, supporting an important role for this stress response in the pathology of DR (18,19). We showed that overexpression of α-crystallins protects retinal neurons in culture and that diabetes dramatically reduces the solubility and alters the subcellular localization of Neurodegeneration is a central aspect of the early stages of diabetic retinopathy, the primary ocular complication associated with diabetes.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations